Government Expenditure and Poverty in Indonesia - Sasana, H; Kusuma, P (KnE Social Sciences, 2018)
Poverty is a complex and multidimensional problem, so that the necessary effort or Government policies that is sustainable and synergistic to reduce the number of poor population. This study aims to analyze the determinants of poverty in Indonesia based on economic and social indicators. It is using linear regression analysis tool by using multiple Fixed-Effects Model (FEM). The results of the study found that economic growth has a positive effect against poverty in Indonesia. While the government are spending, per capita income, labor force participation and effect negatively to poverty in Indonesia. Keywords: poverty, economic growth, expenditure, labor force, income per capita